2015
DOI: 10.1590/0037-8682-0037-2015
|View full text |Cite
|
Sign up to set email alerts
|

Occult HBV infection status among chronic hepatitis C and hemodialysis patients in Northeastern Egypt: regional and national overview

Abstract: Introduction:Occult hepatitis B infection (OBI) is considered to be one of the major risks for patients suffering from end-stage renal disease (ESRD) on regular hemodialysis (HD) and patients with chronic hepatitis C virus (HCV) infection. This study compared the prevalence of OBI among these two high-risk groups in the Suez Canal region, Northeastern Egypt, to obtain a better national overview of the magnitude of OBI in this region. Methods: Serum samples were collected from 165 HD patients and 210 chronic HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
(26 reference statements)
4
15
0
Order By: Relevance
“…Several reports have shown a significant association between OBI and HCV infection . As both HBV and HCV share the same transmission mode, a higher prevalence of co‐infections seems plausible especially in endemic areas or in persons with parental risk factors such as haemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown a significant association between OBI and HCV infection . As both HBV and HCV share the same transmission mode, a higher prevalence of co‐infections seems plausible especially in endemic areas or in persons with parental risk factors such as haemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown a significant association between OBI and HCV infection. [36][37][38] As both HBV and HCV share the same transmission mode, a higher prevalence of co-infections seems plausible especially in endemic areas or in persons with parental risk factors such as haemodialysis. In our study, not unexpectedly, the anti-HCV prevalence was higher in the CHD cohort (3.7%) and KTx cohort (4.8%) than in the general German population.…”
Section: Serum Only Pbmcs Only Serum + Pbmcsmentioning
confidence: 99%
“…In addition, HCV “core”, NS2 and NS5A proteins could strongly inhibit HBV replication[ 34 , 43 , 49 - 51 ]. Table 1 shows the distribution of OBI among patients with HCV infection[ 52 - 66 ].…”
Section: Possible Obi Outcomes Of Lamivudine or Interferon Therapymentioning
confidence: 99%
“…have previously stated that detection of anti‐HBc alone (isolated anti‐HBc) may reflect unrecognized OBI in patients undergoing HD . Furthermore, previous studies have shown that patients who are positive for total anti‐HBc and/or anti‐HBs may have OBI . To the best of our knowledge, this is the first study to determine the prevalence of precore mutation (2/28; 7.1%) among patients undergoing HD in Egypt.…”
Section: Discussionmentioning
confidence: 86%